63.7k views
4 votes
Solve 5y+34 = -2(-7y+1)

User JGFMK
by
5.2k points

2 Answers

6 votes
  • Answer:

y = 4

  • Explanation:

Hi there !

5y + 34 = - 2(-7y + 1)

5y + 34 = (-2)(-7y) + (-2)(+1)

5y + 34 = 14y - 2

→ move ←

sign changed

34 + 2 = 14y - 5y

36 = 9y

y = 36 : 9

y = 4

Good luck !

User Shihongzhi
by
5.6k points
6 votes

Answer:

y=4

Explanation:

The first step to solving this equation is to get rid of the brackets, which we do by multiplying each term on the brackets with the term outside it, so:

5y+34=-2*-7y+-2*1

Then we multiply and merge any like terms:

5y+34=14y-2

Now we need to move all y terms to one side and numbers on the other which we do by reversing the sign:

5y+34-5y+2=14y-2+2-5y

This leave us with:

9y=36

Now all that's left to do is divide both sides by 9 so we are left with:

y=4

Hope this helped!

User Anthony Cannon
by
6.2k points